Land Tenure Insecurity Constrains Cropping System Investment in the Jordan Valley of the West Bank - Caulfield, Mark E.; Hammond, James; Fonte, Steven J.; Wijk, Mark T. van (MDPI, 2020)
The annual income of small-scale farmers in the Jordan Valley, West Bank, Palestine remains persistently low compared to other sectors. The objective of this study was therefore to explore some of the main barriers to reducing poverty and increasing farm income in the region. A “Rural Household Multi-Indicator Survey” (RHoMIS) was conducted with 248 farmers in the three governorates of the Jordan Valley. The results of the survey were verified in a series of stakeholder interviews and participatory workshops where farmers and stakeholders provided detailed insight with regard to the relationships between land tenure status, farm management, and poverty. The analyses of the data revealed that differences in cropping system were significantly associated with land tenure status, such that rented land displayed a greater proportion of open field cropping, while owned land and sharecropping tenure status displayed greater proportions of production systems that require greater initial investment (i.e., perennial and greenhouse). Moreover, as confirmed by a structural equation model and the interviews and workshops these associations led to significant differences in farm income and progress out of poverty index scores. However, while sharecropping farms enjoyed the benefits of being able to invest in longer-term, more profitable farming strategies, questions were raised regarding the sustainability of these farms as well as the vulnerability of the farming households that manage the land. We concluded that small-scale agricultural development in the Jordan Valley relies on farming households achieving more secure land tenure and that rural development agencies should prioritise farming households that rent land and practice open field cropping systems within their projects and programmes.